Intravital Microscopy of the Parietal Peritoneum Microcirculation and the Role of Syndecan-1 in Staphylococcus aureus Infection in Peritoneal Dialysis - Kowalewska, Paulina M (My University, 2014)
Chronic peritonitis contributes to technique failure in peritoneal dialysis (PD), an effective replacement therapy for chronic kidney failure. Staphylococcus aureus infection is one of the most common causes of peritonitis in PD. Interestingly, mice deficient in the cell surface heparan sulfate proteoglycan, syndecan-1, were reported to clear S. aureus corneal infection more effectively than wild-type mice. The objectives of this study were to examine the protein expression and role of syndecan-1 in leukocyte recruitment, chemokine presentation and S. aureus infection in the microcirculation underlying the parietal peritoneum in wild-type and syndecan-1-/- mice. Immunofluorescence intravital microscopy (IVM) of the parietal peritoneum microcirculation revealed that syndecan-1 was localized to the subendothelial region of venules and the mesothelial layer but does not regulate leukocyte recruitment and is not necessary for presentation of the chemokine MIP-2 in peritoneal venules. IVM was also used to study the effects of a conventional PD solution injected through a peritoneal catheter in a mouse PD model. After 6 weeks of dialysis, the peritoneal catheter implant increased leukocyte rolling and extravasation, fibrosis and angiogenesis in the parietal peritoneum independently from the dialysis solution treatment. Furthermore, the role of syndecan-1 was examined using a 4 week PD model. Four hours after infection with S. aureus through the dialysis catheter or intraperitoneal injection, the dialyzed syndecan-1-/- mice were more susceptible to S. aureus infection than undialyzed syndecan-1-/- controls and wild-type animals. IVM showed that in S. aureus infection, syndecan-1 was removed from the subendothelial surface of peritoneal venules but syndecan-1 deficiency did not affect leukocyte recruitment during S. aureus infection. This study indicates that syndecan-1 in the peritoneum and microcirculation is not a regulator of inflammatory responses but is crucial for providing a barrier to S. aureus infection, which may have important implications for susceptibility to S. aureus infections in PD.
Role of Syndecan-1 in Peritoneal Dialysis and Peritonitis
Keywords: peritoneal dialysis; proteoglycans; leukocytes; chemokines; adhesion molecules; endothelium